Engineered liposomes bearing camptothecin analogue for tumour targeting: in vitro and ex-vivo studies. (2nd October 2021) - Saraf, Shivani; Jain, Ankit; Tiwari, Ankita; Verma, Amit; Jain, Sanjay K.
Abstract: Topotecan (TPT) is a semi-synthetic, water-soluble derivative of camptothecin, which inhibits the action of topoisomerase I in the S-phase of the cell cycle leading to cell death. For the effective delivery of TPT to cancer cells, pH-sensitive sialic acid modified liposomes were developed. These liposomes were prepared by the thin-film hydration method using the active loading technique. Vesicle size, polydispersity index (PDI), zeta potential, and percentage entrapment efficiency were determined to be 167  ±  3.78  nm, 0.243, −8.39  mV, and 79.88  ±  1.67%, respectively. The pH-sensitive sialic acid (SA) conjugated liposomes enhanced the drug release at acidic pH 4 (92.33  ±  4.21%) as compared to physiological pH 7.4 (63.11  ±  4.51%). A Sulforhodamine B (SRB) cytotoxicity assay was performed in Murine sarcoma S180 cell lines and the GI50 value of free TPT, Lipo, P-Lipo, SA-P-Lipo, and Adriamycin (ADR) were determined to be 10.07  ±  0.15, 27.33  ±  1.01, 28.76  ±  0.87, 15.7  ±  0.45, and 11.5  ±  0.21  µg/mL, respectively. Results obtained from the apoptosis study revealed that cell death by a combination of early apoptosis and apoptosis caused by SA-P-Lipo was ∼24 fold higher than the control. These results demonstrated that pH-sensitive sialic acid conjugated liposomes will be a potential formulation for improving the antitumor efficacy of TPT. However, further research is necessitated to expedite its applicability in clinical regimen in order to ascertain its safety and efficacy.